Outdoor Wood Finishing: A Review on Making Wood Resistant to Moisture, Ultraviolet Light, and Degradation - P. Frederik Laleicke; Martin A. Hubbe (BioResources)
This article reviews published literature related to the coating of wood surfaces for external applications. Research has shown that a wide range of procedural steps and components in coating formulations can contribute to increasing the effective service life of the coating as well as to maintaining the quality of the coated wood surfaces. Published findings support the idea that the commonly observed service life of painted wood surfaces exposed to outdoor weather can be significantly increased by dedicated application of such measures as optimized sanding, the use of an effective primary coat, the type of resin in the finish coat, increasing the number of layers of the finish coat, and a wide range of issues related to formulation of the finish coat. Even if a majority of contractors and homebuyers continue to prefer such options as vinyl or aluminum siding, the market opportunities remain very large for clients who prefer to rely on coatings and wood products for exterior surfaces of buildings and other exterior wood items.